Biosynthesis of polyesters and their application on cellulosic fibers - Zhao, Xiaoman (2019)
This chapter intends to be an overview about the biosynthesis of polyesters and their applications with special focus on the coating of cellulose fibers. A review about the surface engineering underlying the cellulose fiber modification is the starting point of the chapter. Afterward, the different techniques for the biosynthesis of polyesters are highlighted, including the end-functionalized polymer synthesis with different functional initiators or terminators. The state-of-the-art about chemoenzymatic polymerization was reviewed focusing on the synthesis of polymers, which are generally described as hardly produced via conventional single methods. The final part of the chapter focuses on the techniques of cotton coating namely chemical grafting, physical coating, irradiation-induced grafting polymerization, enzymatic coating, among others. The significance and work perspectives are also discussed, as well as the major polyester biosynthesis applications.